2017
DOI: 10.1016/j.jns.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Global brain atrophy and metabolic dysfunction in LGI1 encephalitis: A prospective multimodal MRI study

Abstract: Background: Chronic cognitive deficits are frequent in leucin-rich glioma-inactivated 1 protein (LGI1) encephalitis. We examined structural and metabolic brain abnormalities following LGI1 encephalitis and correlated findings with acute and follow-up clinical outcomes. Methods:Nine patients underwent prospective multimodal 3 Tesla MRI 33.1±18 months after disease onset, including automated volumetry, diffusion tensor imaging (DTI) and magnetic resonance spectroscopy (MRS). Data were compared to 9 age-and sex-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The results indicated that abnormal brain connectivity and microstructure in brain areas associated with memory, cognition and motion dysregulation circuits were related to the generic risk of anti-LGI1 encephalitis, which makes it a potential endophenotype for anti-LGI1 encephalitis. The most commonly brain alteration in anti-LGI1 encephalitis was hippocampal atrophy in the previous MRI studies (Finke et al, 2017;Miller et al, 2017;Szots et al, 2017). Correspondingly, we identified the decreased functional connectivity in hippocampus and its correlation with the disease severity in this study.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The results indicated that abnormal brain connectivity and microstructure in brain areas associated with memory, cognition and motion dysregulation circuits were related to the generic risk of anti-LGI1 encephalitis, which makes it a potential endophenotype for anti-LGI1 encephalitis. The most commonly brain alteration in anti-LGI1 encephalitis was hippocampal atrophy in the previous MRI studies (Finke et al, 2017;Miller et al, 2017;Szots et al, 2017). Correspondingly, we identified the decreased functional connectivity in hippocampus and its correlation with the disease severity in this study.…”
Section: Discussionsupporting
confidence: 62%
“…The microstructural integrity impairments of the hippocampus (Finke et al, 2017), corona radiata, capsula interna and corpus callosum (Szots et al, 2017) were found in patients with anti-LGI1 encephalitis in the DTI studies. The magnetic resonance spectroscopy (MRS) revealed lower glutamine/glutamate white matter (WM) levels compared with controls (Szots et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The target molecules of these autoantibodies play important roles in synaptic signal transmission and neuronal plasticity. The autoimmune reaction to these antigens in the majority of cases leads to epileptic seizures and neuropsychiatric symptoms (Table ) (Celicanin et al, ; Fukata, Yokoi, & Fukata, ; Honnorat & Plazat, ; van Sonderen, Petit‐Pedrol, Dalmau, & Titulaer, ; Szots et al, ). In autoimmune encephalitis (AIE), the autoantibodies bind to the extracellular epitopes of the neuronal cell surface receptors or their associated proteins, which can lead to alteration of the structure and function of target antigens by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%